Nasal mucociliary transportability of male and female smokers - Uzeloto, Juliana Souza [UNESP]; Ramos, Dionei [UNESP]; C.F. Freire, Ana Paula [UNESP]; G.D. Christofaro, Diego [UNESP]; Mara C. Ramos, Ercy [UNESP] (Elsevier, 2018)
Introduction: Female smoker's present increased susceptibility to several diseases when compared to the opposite gender. However, there are no studies showing differences in nasal mucociliary transport behavior between male and female smokers. Objective: To compare the nasal mucociliary transportability in male and female smokers and non-smokers, taking into consideration age, anthropometric data, smoking load and pulmonary function. Methods: The analysis included 139 individuals (33 men and 37 women smokers and 32 men and 37 women non-smokers). All participants answered an initial interview to obtain personal data and smoking load. Anthropometric data and carbon monoxide in the exhaled air were assessed. Individuals also performed pulmonary function test and Saccharin Transit Time test. To compare saccharin transit time values between men and women, smokers and non-smokers, stratification of all independent variables was performed (sociodemographic, smoking and respiratory variables) into two categories: below and above the median values. Results: There was no difference between men and women, smokers and non-smokers, regarding nasal mucociliary transportability. Significant differences were only observed between non-smokers. Among those with less forced vital capacity values (<97.37% of predicted), women presented mucociliary transport faster than men. Moreover, it was observed influence of BMI and COex (women smokers), FCV and FEV1 (men non-smokers) and FEF25–75% (women non-smokers) on saccharin transit time values. Conclusion: Based on the findings of this study, nasal mucociliary transport in male and female adult smokers, apparently healthy, are similar.
Transportabilidade mucociliar nasal de homens e mulheres tabagistas
Keywords: Mucociliary clearance; Mucociliary transport; Saccharin; Sex characteristics; Smoking; Tobacco use disorder